2014
DOI: 10.1186/s12909-014-0271-4
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap - planning Lifestyle Medicine fellowship curricula: A cross sectional study

Abstract: BackgroundThe emerging field, Lifestyle Medicine (LM), is the evidence-based practice of assisting individuals and families to adopt and sustain behaviors that can improve health. While competencies for LM education have been defined, and undergraduate curricula have been published, there are no published reports that address graduate level fellowship in LM. This paper describes the process of planning a LM fellowship curriculum at a major, academic teaching institution.MethodsIn September 2012 Harvard Medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…Further, in 2012, during the study, the Israeli Society of Lifestyle Medicine (ISLM) was founded by three of its investigators (RP, AT-O, LM), and it was approved as a society within the IAFP by the Israeli Medical Association 29. As discussed in other manuscripts that describe LM as inclusive in a family medicine faculty's career path,30 most of this society's board consists of the programme's graduates.…”
Section: Discussionmentioning
confidence: 99%
“…Further, in 2012, during the study, the Israeli Society of Lifestyle Medicine (ISLM) was founded by three of its investigators (RP, AT-O, LM), and it was approved as a society within the IAFP by the Israeli Medical Association 29. As discussed in other manuscripts that describe LM as inclusive in a family medicine faculty's career path,30 most of this society's board consists of the programme's graduates.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of US medical schools do not include LM as a regular part of their undergraduate training 19 and initiatives offering lifestyle-medicine as optional courses are reported as novelties. 20 Yet, recently evolved LM curricula 21,22 and implementation initiatives 22-24 instill hope that a change may be underway.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has indicated that live face-to-face CME formats, as compared with print and Web-based delivery systems, are often preferred 58 and have equal or greater impact on physician behaviors. 59 Although Web-based modules have become popular, live in-person lecture formats still constitute the majority of programs through all levels of UME, 11 GME, 37 and CME. 15 …”
Section: Delivery Methodsmentioning
confidence: 99%
“…36 However, when polled, LM stakeholders determined nutrition, physical activity, behavioral change techniques, stress resiliency, and personal behavior as equally important domains of a LM fellowship curriculum and more important than smoking cessation to be included in future LM fellowship curricula. 37 …”
Section: Evolving Curriculum Topicsmentioning
confidence: 99%
See 1 more Smart Citation